ADVANCEMENTS IN HIGHER EDUCATION: THE IMPACT OF ACADEMIC FREEDOM ON UZBEKISTANS UNIVERSITIES AND ACADEMIC PROGRAMS - Юлдашев, Feruz (Центр Научных Публикаций (buxdu.uz), 2024)
The trend of competition development up to the current environment has necessitated reforms throughout the higher education system, specifically the implementation of academic autonomy principles. One of the main conditions for achieving competitiveness in today’s economically modernized and innovation-driven industrial and service sectors is the production of new and multifunctional goods, comprehensive service provision, and further enhancement of existing opportunities. Of course, long-term government support is also necessary for this. Improving the quality of education by adhering to fair competition criteria, considering its systematic development, and continuously refining mechanisms for timely decision-making based on the capabilities of HEIs is one of the most pressing issues in contemporary science. Achieving the expected level of education quality is the primary task.